Adolescents' Reward‐related Neural Activation: Links to Thoughts of Nonsuicidal Self‐Injury. Issue 1 (19th January 2018) - Poon, Jennifer A.; Thompson, James C.; Forbes, Erika E.; Chaplin, Tara M.
Abstract : Adolescence is a critical developmental period marked by an increase in risk behaviors, including nonsuicidal self‐injury (NSSI). Heightened reward‐related brain activation and relatively limited recruitment of prefrontal regions contribute to the initiation of risky behaviors in adolescence. However, neural reward processing has not been examined among adolescents who are at risk for future engagement for NSSI specifically, but who have yet to actually engage in this behavior. In the current fMRI study ( N =  71), we hypothesized that altered reward processing would be associated with adolescents' thoughts of NSSI. Results showed that NSSI youth exhibited heightened activation in the bilateral putamen in response to a monetary reward. This pattern of findings suggests that heightened neural sensitivity to reward is associated with thoughts of NSSI in early adolescence. Implications for prevention are discussed.